THE USE OF JARGON IN GARENA FREE FIRE ONLINE GAME: SOCIOLINGUISTICS APPROACH - Muhammad Ibnu Bayhaqi; Zuindra, Zuindra; Muhammad Kiki Wardhana (Cahaya Ilmu Bangsa Institute, 2024)
This study investigated the sociolinguistics phenomenon in terms of jargon. This study investigates the usage of jargon in Garena Free Fire Online Game: A Sociolinguistic Approach. This study looked at two characteristics of jargon used in the online game Garena Free Fire: its form and purpose. The objectives of this study are to identify types of jargon used in the online game Garena Free Fire and to define the function of the jargon that appears in Garena. Online games offer an alternate way to engage oneself while or after activities, and researchers are using Garena Free Fire to perform jargon research. This study makes use of qualitative research methods. The data were collected from Garena Free Fire while also taking note of the vocabulary used in this study. The researcher collects data using Kridalaksana's (2008) theory for jargon forms and Brown, S., and Attardo's (2000) theory for jargon functions. The findings of this study are as follows: (1) There are 30 data points for three types of jargon: twelve for phrases, ten for abbreviations, and eight for words. (2) Based on the first function, jargon were provided to speakers of specialized domains with clear, unambiguous terms to refer to their activities with sixteen data, and based on the second function, jargon were provided to speakers of a subgroup with a means